Quality control of metallized polymer films after automated laser perforation - P. A. Vyatlev; E. V. Leun; D. V. Sergeev; V. K. Sysoev (Омский научный вестник)
The article discusses the control of parameters of laser-perforated metallized polymer films used in the manufacture of screenvacuum thermal insulation (SVTI) mats of spacecraft. The design, operating principle and operating mode of the laser perforator are described. It is shown that the most important operational parameters of perforated SVTI films are strength and dust release. Experimental studies have shown that laser perforation leads to increased strength and reduced dispersion for different samples of films SVTI compared with similar indicators for manual mechanical or semi-automatic thermomechanical perforation. When measuring the profile of the edge of the perforated hole, the optimal geometric parameters of the carbon Deposit zone consisting mainly of carbon corresponding to the effective mode of laser perforation and the maximum strength are determined. It is also shown experimentally that laser perforation does not lead to an increase in the dust release of SVTI films.